Penerapan Sistem Manajemen K3 Dan Lingkungan Di Industri Otomotif - Matondang, Ahmad Baihaqie; Putra, Ilham Anjassetya; Simbolon, Astri; Yansyah, Andre; Rufandi, Muhamad; Tua Natalis Situmorang, Marningot (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
The automotive industry is one of Indonesia’s strategic sectors with a high risk of workplace accidents and environmental impact. Over the past decade (2015–2025), the government and industry stakeholders have increasingly focused on implementing Occupational Health and Safety Management Systems (OHSMS, known in Indonesia as SMK3) and Environmental Management Systems (EMS, known as SML) based on international standards (e.g., ISO 45001 and ISO 14001). This study presents a systematic literature review on the implementation of OHS management systems and environmental management systems in Indonesia’s automotive industry during the last ten years. The review results show a rising trend in OHSMS/EMS adoption driven by stricter regulations and global market demands, with many domestic automotive companies achieving occupational safety and environmental certifications. OHSMS implementation has been shown to reduce workplace accident rates and enhance productivity, whereas EMS adoption helps control pollution and improve resource efficiency. However, key challenges persist, including a lack of top management commitment, limited resources, a safety and environmentally conscious culture that is not yet firmly established, and the need to increase employee participation. Case studies of leading automotive firms highlight best practices in integrating OHSMS and EMS, but the sector overall still requires continuous efforts to strengthen its safety culture and environmental performance.